GRAMMAR IS ONE OF THE IMPORTANT PARTS IN LEARNING ENGLISH - Azizova Makharam Rashitovna (Bright Mind Publishing, 2025)
This article is devoted to the study of language as a part of general knowledge. In the study of language, grammar occupies a central position. But there is also a practical reason to emphasize the study of grammar it is easy to learn to use dictionaries by yourself to find the pronunciation, spelling, or meaning of words, but it is to consult grammar books without a considerable knowledge of grammar.
Keywords: Study, general knowledge, affect, understand, practical application, grammar, dictionary, pronunciation, description, phonetic.